2013
DOI: 10.1021/ct400140n
|View full text |Cite
|
Sign up to set email alerts
|

Lennard-Jones Lattice Summation in Bilayer Simulations Has Critical Effects on Surface Tension and Lipid Properties

Abstract: The accuracy of electrostatic interactions in molecular dynamics advanced tremendously with the introduction of particle-mesh Ewald (PME) summation almost 20 years ago. Lattice summation electrostatics is now the de facto standard for most types of biomolecular simulations, and in particular, for lipid bilayers, it has been a critical improvement due to the large charges typically present in zwitterionic lipid headgroups. In contrast, Lennard-Jones interactions have continued to be handled with increasingly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(216 citation statements)
references
References 44 publications
6
210
0
Order By: Relevance
“…18 The structures simulated originally come from the work of Hub et al 25 These structures contain 128 POPC molecules and 5,262 SPC 26 water molecules. The systems were simulated for 100 ns at 298 K, using a time step of 2 fs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 The structures simulated originally come from the work of Hub et al 25 These structures contain 128 POPC molecules and 5,262 SPC 26 water molecules. The systems were simulated for 100 ns at 298 K, using a time step of 2 fs.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work 18 we showed that when using LJ-PME with LB combination rules we only obtain 25% of the performance we get by using cutoffs, which makes it hard to motivate its use. However, we also noted that by using geometric combination rules for the reciprocal part of the potential, the performance could be increased up to almost 80% of the performance obtained using a twin-range 10/16Å cutoff.…”
Section: Performancementioning
confidence: 97%
See 2 more Smart Citations
“…Although these kinds of methods may be applied for any kind of power-law potential, they have not until recently been effectively implemented for dispersion interactions in standard molecular dynamics software. 3 Therefore, it is still of interest to calculate long-range corrections. The cutoff affects energies, forces and pressures.…”
Section: Introductionmentioning
confidence: 99%